Effects of PPy, GO and PPy/GO composites on the negative plate and on the high-rate partial-state-of-charge performance of lead-acid batteries. (10th October 2016) - Yang, Huan; Qiu, Yubing; Guo, Xingpeng
Highlights: GO obviously accelerates the H2 evolution in negative plates but PPy impedes it. Proper PPy/GO (PG) can effectively inhibit the H2 evolution in negative plates. GO and PG1 (weight ratio of pyrrole to GO = 1:1) largely increase HRPSoC cycle life. GO and PG1 obviously impede the growth of PbSO4 crystals in negative plates. Abstract: In order to improve the high-rate partial-state-of-charge (HRPSoC) performance of lead-acid batteries for hybrid-electric vehicles, graphene oxide (GO), polypyrrole (PPy) and three PPy/GO composites with different weight ratio of pyrrole to GO ( m py / m GO ) were selected as additives to form negative plates and simulated test cells. The effects of these additives on the electrochemical performance and the microstructure of the negative plate and on the HRPSoC cycle performance of the simulated test cell were investigated. The results indicate that the microstructure of the negative plate is changed with the addition of different additives. GO significantly increases the hydrogen (H2 ) evolution ability of the negative plate, while PPy has the opposite effect. The incorporation of the proper content of PPy with GO can effectively inhibit the H2 evolution of the negative plate. Moreover, adding different additives in the negative plate also decreases its total impedance, accelerates the redox processes between Pb and PbSO4 on it and increases its specific capacitance. GO and the PPy/GO composite with m py / m GO  = 1:1 (PG1 ) can significantly increase the HRPSoC cycle life of the simulated test cell. Considering the H2 evolution performance and the HRPSoC cycle performance, the PPy/GO composites with a medium m py / m GO ratio, such as PG1, may be the appropriate additives for the negative plate of lead-acid batteries.